Jaw kinematics and mandibular morphology in humans. Issue 139 (February 2020) - Laird, Myra F.; Ross, Callum F.; O'Higgins, Paul
Abstract: Understanding the influence of feeding behavior on mandibular morphology is necessary for interpreting dietary change in fossil hominins. However, mandibular morphology is also likely to have an effect on feeding behavior, including jaw kinematics. Here we examine the relationships between mandibular morphology and jaw kinematics in humans using landmark-based morphometrics to quantify jaw movement. Three-dimensional movements of reflective markers coupled to the mandible and cranium were used to capture jaw movements while subjects chewed cubes of raw and cooked sweet potato. Geometric morphometric methods were adapted to quantify and analyze gape cycle motion paths. Gape cycles varied significantly across chewing sequences and between raw and cooked sweet potato. Variation in gape cycle size and shape is related to the width (intergonial distance) and length of the mandible. These results underline the fact that jaw kinematic variation within and between taxa is related to and may be influenced by mandibular morphology. Future studies examining kinematic variation should assess the influence of morphological differences on movement.